(untitled) (EAAE Annual Conference Proceedings, 2025)
Education takes time. Studio-based learning recognises this and provides a pedagogical environment that can afford a slower, more immersive, deliberate experience. This paper presents previously unpublished research from the Studio Properties research project. It explores how daily patterns, project cycles, varying intensities of the studio, and designing alongside others are time-based architectures that structure learning in the studio. However, the difficulty for educators is that such architectures are often invisible, tacit, and assumed, meaning they can be easily dismissed under resources and cost pressures in contemporary higher education contexts. The Studio Properties book makes tacit and explicit the properties of studio for educators, giving them tools to examine, surface and articulate the value of studio in the face of increasingly commoditised higher education environments. In particular, it recognises the value of studio as offering: the time and place for immersion and the long durée of a studio experience; the textures of activity in studio as rhythms acting as curricular entities; student agency to create their own learning spaces. Studio Properties challenges reductive ideas of education as immediate, standardised, or transactional and instead argues for the value of studio as a deliberate, polyrhythmic pedagogy.